2019
DOI: 10.1088/1757-899x/523/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Investigating public perceptions and its implication toward Trans Koetaradja policy considering latent motivation

Abstract: Urban bus system so-called Trans Koetaradja (TK) has been considered and piloted as a way to mitigate motorcycles and cars dependency in Banda Aceh, capital of Aceh Province. It is assumed that the effectiveness of the such proposed policy would be useful if the public acceptance of this policy has a positive response. Therefore, this study intends to investigate the attitudes of the public in responding to such proposed policy. The data were collected within line 3 and line 4 of TK that is City Center - Mata … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The trial run corridors of TK are within the city of Banda Aceh (see Fig. 1a) as the city heavily relies on private modes such as cars and motorcycles [9], [10]. The target area of this study is corridor 1 (red), 3 (dark blue), and 4 (yellow) as shown in Fig.…”
Section: Datamentioning
confidence: 99%
“…The trial run corridors of TK are within the city of Banda Aceh (see Fig. 1a) as the city heavily relies on private modes such as cars and motorcycles [9], [10]. The target area of this study is corridor 1 (red), 3 (dark blue), and 4 (yellow) as shown in Fig.…”
Section: Datamentioning
confidence: 99%
“…Therefore, policies reflecting the needs of certain income groups need to be formulated to ensure impartiality during the implementation of the full-charge in the bus system and make it more affordable. It is also better to understand the travel behavior of residents to achieve successful and more efficient transport planning, particularly dealing with behavioral adopting the commuting trip in emerging cities [18][19][20][21].…”
Section: A122mentioning
confidence: 99%
“…Recent studies have been attempted on quantifying of perceived quality of service by passengers to distinguish the most probable influencing factors of service quality attributes. According to [7,8,10], public acceptance for the proposal of Trans Koetaradja as new system of urban public transport in Banda Aceh city was found to be significantly high but the people are unable to make use of it effectively due to its limited routes. This means that there is a need for public transport administrators to classify the elements of service quality considered to be pertinent to public/users and use detailed strategic and Sugiarto, et al -The relative importance of bus system"s perceived service quality (PSQ) attributes among public and private mode users in Indonesia operational policies to attract new users.…”
Section: Introductionmentioning
confidence: 99%